Long Non-coding RNA Expression Profile and Functional Analysis in Children With Acute Fulminant Myocarditis - Liu, Qingqing; Kong, Yaru; Han, Bo; Jiang, Diandong; Jia, Hailin; Zhang, Li (Frontiers in Pediatrics, 2019)
Long noncoding RNA (lncRNA) has been shown to be associated with human diseases. To study the role of lncRNA in the pathogenesis mechanism of acute fulminant myocarditis (AFM), we used a microarray to analyze lncRNA and messenger RNA (mRNA) expression in leukocyte samples from AFM patients and normal children. In total, using a 2/0.5-fold change and p<0.05 as the cutoff, we found that 3101 lncRNAs and 2170 mRNAs were differentially expressed in AFM. Quantitative real-time polymerase chain reaction (RT-qPCR) was used to verify the microarray data. Eight differentially expressed molecules were randomly selected, including 3 upregulated lncRNAs, 3 downregulated lncRNAs and 2 upregulated mRNAs. Among them, 7 expression profiles were cosistent with the microarray results. Gene Ontology enrichment and KEGG pathway analysis were used to investigate biological function. The lncRNA-mRNA coexpression network and lncRNA target predication were performed to study molecular interactions. Our study is the first to use microarrays to study the lncRNA and mRNA expression profiles associated with AFM and indicate that the immune system plays an important role in AFM. The findings may provide a new view of the pathogenesis, diagnosis and therapy of AFM.